How do Hearing Aid Owners Acquire Hearing Aid Management Skills? - Bennett, Rebecca J.; Meyer, Carly J.; Eikelboom, Robert H. (Journal of the American Academy of Audiology, 2019)
Clinical studies have found up to 90% of hearing aid owners demonstrate difficulty with basic hearing aid management tasks and almost 50% of hearing aid owners self-report not receiving enough practical help from their clinician regarding how to use their hearing aid. Although studies have highlighted the overwhelming amount of information and training required to learn how to use a hearing aid appropriately, a gap remains in the literature regarding the range of methods by which hearing aid owners acquire the knowledge and skills for hearing aid use, and whether these approaches are considered beneficial.To gain insight into how both hearing aid owners and hearing health clinicians view the acquisition of hearing aid management skills and the efficacy of currently used methods of hearing aid training.Concept mapping techniques were used to identify key themes, wherein participants generated, sorted, and rated the importance of statements in response to the question “How do hearing aid owners learn the skills required to use, handle, manage, maintain, and care for their hearing aids?”Twenty-four hearing aid owners (aged 56–91 years; 54.2% male) and 22 clinicians (aged 32–69 years; 9.1% male).Participant perspectives were collected via group concept mapping sessions in October 2015. Hierarchical cluster analysis was used to identify themes and develop a framework for understanding how skill acquisition occurs. Participants rated each method of hearing aid skill acquisition as to how beneficial it was and how often it was used.Participants identified 75 unique items describing how hearing aid management skills are acquired within six concepts: (1) Relationship with the clinician, (2) clinician as a source of knowledge and support, (3) hands-on experience, (4) seeking additional information, (5) asking support people for help, and (6) external resources.The results of this study highlight the diverse methods and sources by which hearing aid owners learn the skills necessary to use, manage, and maintain their hearing aids. Significant emphasis was placed on the role of the hearing health clinician to provide training, support, and an ongoing professional relationship, with lesser roles played by family, friends, and other health professionals.
Keywords: hearing aid; hearing aid management; mixed methods; outcomes